An embedded capacitive sensor for in-situ angular detection of micromotor. (August 2021) - Yang, Tianyu; Li, Xiaoshi; Sun, Xiangyu; Wang, Yicheng; Chen, Yu; Gong, Dongdong; Du, Yijia
Abstract: An embedded capacitive sensor in traveling wave ultrasonic motor is proposed for angular detection. Equivalent circuit model of the system is well studied that correlation between sensor structure, parasitic parameters and the property of detection signal is found. Sensor structure is optimized with innovate structural design including multi-layer shielding, planar isolation and differential detection design. The signal-to-noise ratio of the detection signal is found up to 40 ​dB and the angular detection accuracy during step motion is less than 0.1°.